2012
DOI: 10.1186/1742-2094-9-46
|View full text |Cite
|
Sign up to set email alerts
|

Heme activates TLR4-mediated inflammatory injury via MyD88/TRIF signaling pathway in intracerebral hemorrhage

Abstract: BackgroundInflammatory injury plays a critical role in intracerebral hemorrhage (ICH)-induced neurological deficits; however, the signaling pathways are not apparent by which the upstream cellular events trigger innate immune and inflammatory responses that contribute to neurological impairments. Toll-like receptor 4 (TLR4) plays a role in inflammatory damage caused by brain disorders.MethodsIn this study, we investigate the role of TLR4 signaling in ICH-induced inflammation. In the ICH model, a significant up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
264
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 290 publications
(283 citation statements)
references
References 46 publications
(67 reference statements)
10
264
2
3
Order By: Relevance
“…In addition, activation of TLRs and downstream inflammatory signaling, particularly of the TLR-4 pathway, can be triggered by free hemin in some models. [22][23][24] In summary, the definitive pathophysiology of extracellular Hb is dependent on timing, quantity, and tissue localization of Hb/ hemin exposure in a specific clinical condition and may result from cumulative effects largely described by the 4 mechanisms discussed in the sections above. For example, systemic and, to some extent, pulmonary hypertension is the most apparent and readily measurable effect of free Hb after intravascular hemolysis.…”
Section: Mechanism 2: No and Oxidant Reactionsmentioning
confidence: 99%
“…In addition, activation of TLRs and downstream inflammatory signaling, particularly of the TLR-4 pathway, can be triggered by free hemin in some models. [22][23][24] In summary, the definitive pathophysiology of extracellular Hb is dependent on timing, quantity, and tissue localization of Hb/ hemin exposure in a specific clinical condition and may result from cumulative effects largely described by the 4 mechanisms discussed in the sections above. For example, systemic and, to some extent, pulmonary hypertension is the most apparent and readily measurable effect of free Hb after intravascular hemolysis.…”
Section: Mechanism 2: No and Oxidant Reactionsmentioning
confidence: 99%
“…We previously showed that inflammatory injury can be induced by the activation of TLR2/TLR4 dimers, which subsequently activated NF-kB through MyD88 signaling (30,31). Recent studies have indicated that A20 can disturb ubiquitin enzyme complexes that are important for inhibiting NF-kB activation in TLR4 signaling.…”
Section: /2mentioning
confidence: 99%
“…Evidence from intracranial hemorrhage models suggests that hemoglobin and heme released from red blood cells enter the brain parenchyma and free iron from further degradation of the heme molecule, disrupts cellular integrity and function via increased oxidative stress. [106][107][108][109] It is also intriguing that heme upregulates TLR4, 110 a gate keeper of the innate immune system and TLR4 mediates disruption of endothelial barrier function. 111 These observations collectively raise the possibility of bleeding and TLR4 being additional mechanisms involved in the vasoregression and impaired repair process after diabetic stroke.…”
Section: Cerebral Neovascularization In Diabetes a Ergul Et Almentioning
confidence: 99%